Key Drivers Significantly Boost Village Financial Management in Indonesia - Winda Ayu Amilliyah; Sarwendah Biduri (Indonesian Journal of Law and Economics Review, 2024)
This study examines how the Internal Control System, Regional Autonomy, and Village Apparatus Competency affect Village Financial Management in line with Law No. 20 of 2018. Using a quantitative approach, data were gathered from 16 villages in Porong District, Sidoarjo, through questionnaires completed by 60 village officials. Multiple linear regression analysis showed that all three factors significantly influence Village Financial Management, explaining 62.9% of its variation. The findings highlight the importance of strong internal controls, autonomy, and competent village apparatus for effective financial management, providing valuable insights for improving village financial performance. Highlights: 1. Internal control, autonomy, and competency significantly affect village financial management.2. Data from 16 villages show these factors explain 62.9% variation.3. Strengthening controls, autonomy, and competency improves village financial performance. Keywords: Village Financial Management, Internal Control System, Regional Autonomy, Village Competency, Law No. 20 of 2018